Moet teologiese opleiding kerklik-konfessioneel wees? - Deist, Ferdinand (Hervormde teologiese studies, 1994)
Should theological education be ecclesiastical and confessional? This article seeks to evaluate the involvement of the church in theological education at universities, and proceeeds from a cosmological rather than a pragmatic perspective. From a cosmological perspective, no university can claim to study universalia while ignoring religious perspectives on reality. The Christian religious perspective therefore has every right to be studied and taught at universities. Since this tradition can be adequately understood only with reference to its own assumptions (as professed by the ecumenical church), theological education has to pay close attention to ecclesiastical and denominational confessions. However, no state-funded theological education at university level may be bound by denominationally biased prescriptions.